Proximity Labeling and Genetic Screening Reveal that DSG2 is a Counter Receptor of Siglec‐9 and Suppresses Macrophage Phagocytosis - Ying Wu; Yuyu You; Tingsong Jiang; Yuqi He; Qingchi Fan; Xinlei Zeng; Ting Li; Yuxing Lu; Liang Qi; Fengxia Zhou; Lingyu Sun; Danyang Wang; et al. (Advanced Science)
Abstract Cancer cells present sialylated glycoconjugates that modulate the activity of various immune cells within the tumor microenvironment through trans interaction with immunosuppressive Siglec receptors. Identifying counter receptors for Siglecs can provide valuable targets for cancer immunotherapy, but it presents significant challenges. Here, the identification of DSG2 (Desmoglein 2) as a dominant counter receptor of Siglec‐9 in melanoma cells is reported, using a workflow that combines the strength of proximity labeling and the advantage of CRISPR knockout screening. It is further demonstrated that the interaction between DSG2 and Siglec‐9 is mainly dependent on sialic acid‐bearing N‐glycans on DSG2. Importantly, blocking trans interaction between DSG2 and Siglec‐9 significantly enhances macrophage phagocytosis of melanoma cells and, to a lesser extent, other cancer cells. The work thus suggests sialylated DSG2 as a potential “don't eat me” signal molecule with therapeutic potentials in cancer immunotherapy.